Effect of Rhodiola Extracts on Learning, Memory Deficits and Micro Structure of Brain Cells Induced by Sleep Deprivation - HUANG ZUO-YI, XUAN ZHAO-BO, HANG SHU-PING, MUHAMMAD ZEESHAN ABBAS, (Journal of Fatima Jinnah Medical University, 2018)
Objective：To Study the effect of Acanthopanax senticosus extract on the brain cell ultrastructure of rats model of sleep deprivation and its learning and memory deficits. Material and Methods: Brain cells ultrastructure were observed by transmission electron microscopy, rat model of sleep deprivation were made by using a modified multiple platform water environmental law, learning and memory ability were assessed by a maze test in rats. Results: In rat model of sleep deprivation group (SD group) there was obvious brain cell injury, learning and memory deficits and increased reaction time as compared to cage control group ( group CC) and tank control group ( group TC) ( p<0.05, p<0.01 ). In treatment group ( ST group ) with Acanthopanax senticosus, the brain cell injury was lighter, learning and memory deficits were reduced and reaction time was shortened ( p<0.05 ) than that in SD group. Conclusion: The results showed that extract of Acanthopanax senticosus can improve brain cells injury induced by sleep deprivation and can improve learning and memory deficits in sleep deprived rats.